Pola Komunikasi PT Apparel One Indonesia Terhadap Produktivitas Karyawan Pada Masa Pandemi Covid-19 - Miftahul Huda; Viro Dharma Saputra; Velani Ayu Ningtyas (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2021)
Communication within the organization that affects assignment. The purpose of this study is to explain the process and flow of communication at PT Apparel One Indonesia during the Covid-19 pandemic. The research method is qualitative, the data sources are primary and secondary data. Data collection techniques with interviews, observation, and documentation. Data analysis technique with reduction, data presentation and conclusion. The results show that communication at PT Apparel One Indonesia is the first downward communication, namely subordinate communication using whatsapp media. Second, upward communication is communication between employees and superiors that is used to report work developments and organizational problems. The third horizontal communication is communication that occurs between employees that is used for work and problem solving.